Thickness dependence of uniaxial anisotropy fields in GaMnAs films. (13th February 2015) - Bac, Seul-Ki; Lee, Hakjoon; Lee, Sangyeop; Choi, Seonghoon; Yoo, Taehee; Lee, Sanghoon; Liu, Xinyu; Furdyna, Jacek
Abstract: Our investigation of thin GaMnAs films with different thicknesses revealed that the magnetic properties of this material strongly depend on film thickness. For this study, a single GaMnAs film was selectively etched, and its properties were then investigated by planar Hall effect measurements. A particularly important conclusion from the results is the emergence of a uniaxial anisotropy field along the [100] crystalline direction, which increases rapidly with increasing film thickness. We argue that such thickness dependence of the [100] uniaxial anisotropy results from the crystal structure of the film, rather than from the effects of the interface between the GaMnAs and the substrate.